Investigation on the deterioration of lead artifacts. A case study on piano keys and their degradation products. Issue 1 (1st April 2022) - Faggiano, A.; Ricciardi, M.; Pironti, C.; Motta, O.; Miele, Y.; Prete, P.; Proto, A.
Abstract: Among musical instruments, Piano is one of the most important and fascinating ones of all years for its completeness from a harmonic point of view and for the importance it has held in the world of classical music of the great composers. In this context, old pianos can be considered as real pieces of art thus their conservation is included in the preservation of cultural heritage. The aim of this work is to study the deterioration of some lead weights of piano keys from an important, luxury and one of the best grand pianos for its characteristics such as construction materials, sound, and craftsmanship. Analytic techniques such as X-ray Diffraction, Fourier Transform-Infrared spectroscopy and Ionic chromatography were employed to characterize the superficial layer of deteriorated lead weights, comparing it with the non-deteriorated ones. Knowing the nature of degradation products is fundamental to evaluate the degradation phenomena occurring over time due to the environmental conditions at which they are exposed and consequently identify the proper conservation strategy of such piece of art and history of music, in order to preserve its original sound and resonance.